Age, diversification and survival in the German machine tool industry, 1953-2002 - Alex Coad; Christina Guenther (Max Planck Institute of Economics, 2011)
We focus on the relationship of age and diversification patterns of German machine tool manufacturers in the post war era. Based on trade journals we track the entire firm populations' product portfolio development throughout each firm's lifetime. We distinguish between minor diversification and major diversification, where these two concepts refer to adding a new product variation within a familiar submarket, or expanding the product portfolio into new submarkets. Our analysis reveals four main insights. First, we observe that firms have lower diversification rates as they grow older, and that eventually diversification rates even turn negative for old firms on average. Second, we find that product portfolios of larger firms tend to be more diversified. Third, with respect to consecutive diversification activities, quantile autoregression plots show that firms experiencing diversification in one period are unlikely to repeat this behavior in the following year. Fourth, survival estimations reveal that diversification activities reduce the risk of exit controlling for various additional firm and industry specific fixed effects and business cycles. These results are interpreted using the Penrosean growth theory.
Keywords: L20; L25; 330; diversification; industry evolution; firm age; firm growth; machine tools; Maschinenbau; Diversifikation; Lebenszyklus; Unternehmenswachstum; Evolutionsökonomik; Deutschland